(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This paper deals with the results of a revision on the genus Lecanopsis Targioni Tozzetti. All the type slides and other specimens from the main European museums and collections have been studied. The revision highlighted synonymies among species and misidentifications of species erroneously placed in this genus. Before the revision the genus included 18 species, but at the end of this study the number of Lecanopsis species was reduced to 11, plus 3 unrecognisable species. In addition, 2 new species have been recently collected in Italy. Little is know about the morphology of young instar of several species. In fact, all developmental stages are known for only two species, namely L. formicarum Newstead and L. clodiensis (Pellizzari). The importance of the 1st_instar nymphs for identifying Lecanopsis at the species level is reported.